A new seismic stratigraphy in the Indian-Atlantic Ocean gateway resembles major paleo-oceanographic changes of the last 7 Ma - Grützner, Jens; Jiménez-Espejo, Francisco J.; Koutsodendris, Andreas (Geochemistry, geophysics, geosystems, 2019)
Abstract The exchange of water masses between the Indian Ocean and the Atlantic constitutes an integral interocean link in the global thermohaline circulation. Long-term changes in deep water flow have been studied using seismic reflection profiles but the seismic stratigraphy was poorly constrained and not resolved for the time period from the late Miocene onward. Here we present results from International Ocean Discovery Program Site U1475 (Agulhas Plateau) located over a sediment drift proximal to the entrance of North Atlantic Deep Water into the Southern Ocean and South Indian Ocean. Site U1475 comprises a complete carbonate-rich stratigraphic section of the last ~7 Ma that provides an archive of climate-induced variations in ocean circulation. Six marker reflectors occurring in the upper 300 m of the drift are identified here for the first time. The formation of these reflectors is mainly due to density changes that are mostly caused by changes in biogenic versus terrigenous sediment deposition. Synthetic seismograms allow age assignments for the horizons based on biostratigraphy and magnetostratigraphy. Prominent reflectors are related to late Pleistocene glacial/interglacial variability, the middle and early Pleistocene transitions, and the onset of the northern hemisphere glaciation. A peculiar early Pliocene interval (~5.3?4.0 Ma) bounded by two reflectors is characterized by fourfold elevated sedimentation rates (>10 cm/kyr) and the occurrence of sediment waves. We argue that this enhanced sediment transport to the Agulhas Plateau was caused by a reorganization of the bottom current circulation pattern due to maximized inflow of North Atlantic Deep Water.
Gesehen am 21.08.2019